Two neuropeptides recruit different messenger pathways to evoke Ca2+ signals in the same cell. - Burdakov, D; Galione, A (2000)
Bombesin and cholecystokinin (CCK) peptides act as signalling molecules in both the central nervous system and gastrointestinal tract [1-4]. It was reported recently that nicotinic acid adenine dinucleotide phosphate (NAADP) releases Ca2+ from mammalian brain microsomes [5] and triggers Ca2+ signals in pancreatic acinar cells, where it is proposed to mediate CCK-evoked Ca2+ signals [6]. Here, for the first time, we have finely resolved bombesin-induced cytosolic Ca2+ oscillations in single pancreatic acinar cells by whole-cell patch-clamp monitoring of Ca2+-dependent ionic currents [6-8]. Picomolar concentrations of bombesin and CCK evoked similar patterns of cytosolic Ca2+ oscillations, but high, desensitising, NAADP concentrations selectively inhibited CCK, but not bombesin-evoked signals. Inhibiting inositol trisphosphate (IP3) receptors with a high concentration of caffeine blocked both types of oscillations. We further tested whether NAADP is involved in Ca2+ signals triggered by activation of the low-affinity CCK receptor sites. Nanomolar concentrations of CCK evoked non-oscillatory Ca2+ signals, which were not affected by desensitising NAADP receptors. Our results suggest that Ca2+-release channels gated by the novel Ca2+-mobilising molecule NAADP are only essential in specific Ca2+-mobilising pathways, whereas the IP3 receptors are generally required for Ca2+ signals. Thus, the same cell may use different combinations of intracellular Ca2+-releasing messengers to encode different external messages.